Diplomacy in Azerbaijan: The Utilisation of Culture in Indonesia’s Diplomacy Practice - Khairunnisa, Brilliant Windy (The Sunan Ampel Review of Political and Social Sciences, 2024)
The utilisation of culture as a dominant tool in Indonesia's diplomacy creates an identity that Indonesia as an archipelago country has diverse cultures within its nation. The cultural performances are also conducted dominantly by Indonesia worldwide instead of other tools of diplomacy including in Azerbaijan which is conducted about 6-10 times a year. This study aims to explain the reason behind Indonesia utilising culture dominantly in diplomacy practice in Azerbaijan. This paper begins by examining the reason why and ends by comparing and exploring culture, tourism and peace values as dominant tools in Indonesian diplomacy practices. This study employs a mixed-method exploratory sequential where content analysis focusing on 'Indonesia's cultural diplomacy' especially through cultural performances worldwide conducted. It concludes that Indonesia has been utilise culture as a tool of diplomacy practice dominated to other tools due to some reasons Indonesia is the biggest archipelago country with thousands of cultures on every island; Indonesia wants to maintain cultural diversity as its identity worldwide; Indonesia holds an “independent and active” foreign policy which stands as a non-align country. Therefore, using cultural diplomacy as part of soft power is the best means to expand its relations with other countries and shape its international image; as a culturally diverse country, Indonesia believes that the value of its culture has strong relations to the tourism sector, peace, and even economic value as part of its national pillar. On the other hand, Indonesia’s embassy in Azerbaijan is counted as young; therefore, building a trust rooted in cultural diplomacy is an essential thing to develop both countries' relations.